Theodor Wiegand in Mitzpe Shivta: Spolia and Heritage Protection Along the Ottoman Military Railway - Lehnig, Sina; Peleg, Michael; Linstädter, Jörg; Bar-Oz, Guy; Gambash, Gil (Archäologischer Anzeiger, 2025)
The late antique/Early Islamic settlement of Mitzpe Shivta (El-Meshrifeh, Khirbet el-Misrafa, Khirbat al-Mushrayfa, Mesrafeh, Mishrafa) in the Negev Desert, a site closely linked to monasticism and pilgrimage, is renowned for its rock-cut rooms and Christian pilgrim inscriptions. Yet, historical photographs unveil a different facet of its history: once adorned with stone-built structures like towers and retaining walls, many of these features no longer endure. While our excavations demonstrated that parts of the site were already destroyed by an earthquake in the 8th-9th century C.E., the German archaeologist Theodor Wiegand suggested that a significant portion of Mitzpe Shivta’s architecture, still visible on older photographs, was obliterated during the construction of the Ottoman Military Railway in Palestine (1915–1916). Our study, integrating archival sources and archaeological surveys, supports Wiegand’s reconstruction. During World War I, the Negev became a border zone between the Ottoman Empire and British Egypt. The railway from Beersheva to Qusseima was built to transport troops and supplies, facilitating Ottoman control of the Suez Canal. Military time pressure, resource shortages, and harsh environmental conditions prompted the extraction of high-quality ashlar masonry from Mitzpe Shivta for the construction of bridges and channels. At the same time, Wiegand, Djemal Pasha and Bedjed Bey sought to implement protective measures to safeguard the threatened archaeology. Exploitation, however, resulted in significant loss of Mitzpe Shivta’s architecture, so later archaeologists focused on its preserved rock-cut rooms. Historical photos provide a fresh perspective on the settlement before the Negev became a theatre of war.